Being Sami: an ethnography of identity through the lens of the Riddu Riđđu festival - Hansen, Klara (The Australian National University, 2015)
Since the 1960s Sami people have been actively seeking recognition of their Indigenous status. The notion of Sami people as Indigenous has developed along with the rise of indigeneity since the Second World War. The push for recognition received a major boost in the late 1970s – early 1980s during the conflict over the proposed Áltá dam. Building the dam would have led to the flooding of the Sami majority village of Máze and disrupted reindeer herding and salmon fishing. The activity against the dam and the attention it gained marked the beginning of traction in political arenas that has since influenced Sami people’s access to rights and recognition as Indigenous. An increasingly articulated part of the process of recognition is the negotiation and transformation of Sami identity including that of Coastal Sami people. Control over Sami identification has gone from being primarily the domain of non-Sami colonisers to that of Sami people themselves. The conditions surrounding presentations, articulations and transformations of Sami identity are explored. This exploration includes an examination of the traits people need to have to present themselves as Sami and have their identities recognised by others, as well as how these traits are expressed in order to gain recognition and rights. Inspired by Brubaker and Cooper (2000), identity is adopted as a category of analysis. This means clearly presenting processes, practices and relationships in terms of their implications for identity. The ethnographic lens through which these issues are examined is principally the Riddu Riđđu festival, an international Indigenous peoples’ festival held in Norway run primarily by Sami people.